The effect of employing chants in correcting the mistakes of the Arabic language grammar for fifth grade female students - Adel, Saja; Malik , Oroba (Al-Adab Journal, 2024)
The current search for disclosure (edit looking for songs), the research sample found a sample of fifth grade primary schoolgirls. In Baghdad Governorate, a sample consisted of (68) A female student from Al-Maroua Elementary School, they were divided into two equal groups (experimental and control) with (34) female students in each group. (40) objective paragraph of the type of multiple choice, with four alternatives, and the two researchers used what suits the study a number of statistical methods, to analyze and process the data, and the results of the study showed that there are statistically significant differences between the experimental group and the control group in the test in favor of the experimental group Thus, the results of the research proved that the use of educational songs has an effective effect in correcting errors Arabic grammar for fifth grade student.